2011
DOI: 10.1103/physrevlett.106.108503
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Emission Monitoring of the Syracuse Athena Temple: Scale Invariance in the Timing of Ruptures

Abstract: We perform a comparative statistical analysis between the acoustic-emission time series from the ancient Greek Athena temple in Syracuse and the sequence of nearby earthquakes. We find an apparent association between acoustic-emission bursts and the earthquake occurrence. The waiting-time distributions for acoustic-emission and earthquake time series are described by a unique scaling law indicating self-similarity over a wide range of magnitude scales. This evidence suggests a correlation between the aging pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 18 publications
1
41
0
Order By: Relevance
“…As a matter of fact-based on the analogy between AE and seismic activity [30][31][32], on the anomalous radiation of geoelectromagnetic waves observed before major earthquakes [33], and on recent experimental studies that measured neutron components exceeding the usual background in correspondence to seismic activity [34]-if we take into account the correlation between acoustic/electromagnetic/NEs and seismic activity, it could be possible to set up a sort of alarm system based on a regional warning network.…”
Section: Discussionmentioning
confidence: 99%
“…As a matter of fact-based on the analogy between AE and seismic activity [30][31][32], on the anomalous radiation of geoelectromagnetic waves observed before major earthquakes [33], and on recent experimental studies that measured neutron components exceeding the usual background in correspondence to seismic activity [34]-if we take into account the correlation between acoustic/electromagnetic/NEs and seismic activity, it could be possible to set up a sort of alarm system based on a regional warning network.…”
Section: Discussionmentioning
confidence: 99%
“…In other quasi-brittle materials such as concrete (Ohtsu, 1996) or wood (Bucur, 2006) the AE technique is commonly used to study and predict failure processes (Johansen and Sornette, 2000). In the field of natural hazards, acoustic signals have been used to investigate earthquake occurrence (Niccolini et al, 2011) and to predict the collapse of a limestone cliff (Amitrano et al, 2005;Got et al, 2010). Girard et al (2012) set up an acoustic sensor network in order to predict failure within rocks and permafrost.…”
Section: Introductionmentioning
confidence: 99%
“…The acoustic waves generated by the nucleation and propagation of cracks allow for the monitoring of the failure process on the meso- and micro scales. Crackling noise is usually characterized by the integrated statistics accumulating all the events of the time series up to failure234567891011121314. Experiments revealed that the probability distribution of the energy of crackling bursts and of the interoccurrence times have power law functional form, which are considered to be the fingerprint of correlations in the microscopic breaking dynamics1234567891011121314.…”
mentioning
confidence: 99%
“…Crackling noise is usually characterized by the integrated statistics accumulating all the events of the time series up to failure234567891011121314. Experiments revealed that the probability distribution of the energy of crackling bursts and of the interoccurrence times have power law functional form, which are considered to be the fingerprint of correlations in the microscopic breaking dynamics1234567891011121314. The value of the exponents measured on different types of heterogenous materials show a surprisingly large scatter between 1 and 2 which has not been captured by theoretical studies12345678910.…”
mentioning
confidence: 99%